Pinna, D.; Galeotti, M. y Mazzeo, R., eds. (2009). Scientific Examination for the Investigation of Paintings : A Handbook for Conservator-restorers. Firenze: Centro Di, 224 pp. - Tascón, Marcos (Universidad Nacional de San Martín. UNSAM Edita, 2014)
Artículo de anuario